2018
DOI: 10.3390/su10072172
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Availability of 4T-APS as a Video Monitor and Radiation Detector in Nuclear Accidents

Abstract: Abstract:In this paper, we present the availability of an active pixel sensor (APS) with four transistors (4T) as a video monitor and radiation detector. Analyzing radiation damage must be one of the first steps in recovering from nuclear accidents, and the radiation response characteristic is the basis for the use of 4T-APS to detect radiation. The goal of this work is to suggest the use of cameras with 4T-APS in widely distributed irradiation detectors. The total ionizing dose (TID) of radiation damage on 4T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Other authors have carried out related relevant research, such as [35], in which fire smoke was detected from video sources; [36], which showed a fire detection system based on artificial intelligence; [37], which detected terrorist actions on videos; [38,39], that showed novel applications to object detection; [40,41], that showed an excellent tracking applications; [42] in which a Real-Time video analysis was made from several sources with interesting results in object tracking; [43] which proposed a secure framework for IoT Systems Using Probabilistic Image Encryption; [44] which showed an Edge-Computing Video Analytics system deployed in Liverpool, Australia; [45] where GPUs and Deep Learning were used for traffic prediction; [46] where a video monitor and a radiation detector in nuclear accidents were shown; [47] where an Efficient IoT-based Sensor Big Data system was detailed.…”
Section: Related Work In Crime Events Video Detectionmentioning
confidence: 99%
“…Other authors have carried out related relevant research, such as [35], in which fire smoke was detected from video sources; [36], which showed a fire detection system based on artificial intelligence; [37], which detected terrorist actions on videos; [38,39], that showed novel applications to object detection; [40,41], that showed an excellent tracking applications; [42] in which a Real-Time video analysis was made from several sources with interesting results in object tracking; [43] which proposed a secure framework for IoT Systems Using Probabilistic Image Encryption; [44] which showed an Edge-Computing Video Analytics system deployed in Liverpool, Australia; [45] where GPUs and Deep Learning were used for traffic prediction; [46] where a video monitor and a radiation detector in nuclear accidents were shown; [47] where an Efficient IoT-based Sensor Big Data system was detailed.…”
Section: Related Work In Crime Events Video Detectionmentioning
confidence: 99%
“…The key issue of MAPS radiation detection is to study its response characteristics to rays or particles. Experiments have confirmed that MAPS is sensitive to single ionized particles and generates radiation-responsive events in pixel arrays [ 7 , 8 ]. Different particles, such as X-rays, γ photons, and α and β particles, show its specific size and shape of typical response events in a frame [ 9 ].…”
Section: Introductionmentioning
confidence: 99%